Rencana dan Pelaksanaan Dana Desa Di Desa Gandu Kecamatan Comal Kabupaten Pemalang Tahun 2015 - 2017 - Lestari, Dwi; ., Turtiantoro (Journal of Politic and Government Studies, 2019)
The purpose of this study was to analyze the process of planning and implementing village funds in the village of Gandu and identifying inhibiting factors in the process of planning and implementing village funds in the village of Gandu, Comal District, Pemalang Regency, 2015-2017. The theory used in this study is the first Planning theory which includes the stages of the planning process, type of planning, the characteristics of planning effectiveness and the benefits of planning. Second, the implementation theory which contains the implementation concept, and the things that affect the success and failure of implementation. The research method used is qualitative research with an analytical descriptive approach, where in obtaining research data carried out through interviews with speakers who are directly related to the object of research. In this study the speakers were taken from the Village Government and the Gandu Village Community.The results of the study showed that the management of village funds in the village of Gandu was carried out based on Permendagri No. 113 of 2014 concerning Management of Village Finance and Permendagri No. 114 of 2014 concerning Village Development Guidelines. In determining development priorities in the village of Gandu it was conducted by deliberation which began from the hamlet level to the village level, but in terms of community participation in the planning process in Gandu village it was still low because both the hamlet and village consultations did not fully involve the community, only certain people. The implementation of Village Fund development activities in the village of Gandu is carried out with self-management for development that is not difficultwhile for development that is difficult to do by cooperating with third parties, namely by using contractor services.The village government in terms of accountability related to the use of village funds to the community has not yet had wide openness, as evidenced by many people who did not know about the existence of village funds in village development, the government also did not make information boards regarding the details of funds used in development. Inhibiting factors in the Village Fund planning process in the village of Gandu, namely frequent planned budget mismatches and their implementation. While the obstacles in the implementation, namely the lack of labor when it coincides with the rice planting season and weather factors are also obstacles when the rainy season.